2019
DOI: 10.3390/ijms20215327
|View full text |Cite
|
Sign up to set email alerts
|

Wounding and UVB Light Synergistically Induce the Biosynthesis of Phenolic Compounds and Ascorbic Acid in Red Prickly Pears (Opuntia ficus-indica cv. Rojo Vigor)

Abstract: The present study evaluated the effects of ultraviolet B (UVB) radiation and wounding stress, applied alone or combined, on the biosynthesis of phenolic compounds and ascorbic acid in the peel and pulp of red prickly pear (Opuntia ficus-indica cv. Rojo Vigor). Whole and wounded-fruit samples were treated with UVB radiation (6.4 W·m−2) for 0 and 15 min, and stored for 24 h at 16 °C. Phytochemical analyses were performed separately in the peel and pulp. The highest phenolic accumulation occurred after storage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Phenylalanine ammonia-lyase (PAL) activity was measured following the method reported by Ortega-Hernández et al (2019). Fresh carrot tissue (4 g) was homogenized with polyvinylpyrrolidone (0.4 g) in ice-cold 50 mM borate buffer (16 mL, pH 8.5) containing β-mercaptoethanol (5 mM) using a tissuemizer.…”
Section: Phenylalanine Ammonia-lyase Enzymatic Activity Determinationmentioning
confidence: 99%
“…Phenylalanine ammonia-lyase (PAL) activity was measured following the method reported by Ortega-Hernández et al (2019). Fresh carrot tissue (4 g) was homogenized with polyvinylpyrrolidone (0.4 g) in ice-cold 50 mM borate buffer (16 mL, pH 8.5) containing β-mercaptoethanol (5 mM) using a tissuemizer.…”
Section: Phenylalanine Ammonia-lyase Enzymatic Activity Determinationmentioning
confidence: 99%
“…Flavonoids and phenylpropanoids possess the ability to resist a variety of adversity stresses such as UV radiation, low temperature, drought, or pathogen [ 21 , 22 , 23 , 24 , 25 , 26 ]. It has been shown that the amount and type of plant phenolics and ascorbic acid in the plant body would respond to a variety of adversities and play an important role in helping plants to withstand adversity stress [ 27 , 28 , 29 ]. Amino acid classes play an important physiological role in promoting plant growth and enhancing plant stress resistance in several ways [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…UV-B radiation can induce oxidative stress, which produces reactive oxygen species ( Ortega-Hernández et al, 2019 ) and then activates the plant ROS scavenging system ( Das and Roychoudhury, 2014 ). Our study results show that the contents of MDA and H 2 O 2 in M. bealei leaves were increased after exposure to UV-B radiation, and correspondingly, the activity of POD and SOD and T-AOC under the UV-B radiation was significantly improved ( p < 0.05), which was significant for the detoxification of oxidants produced by UV-B ( Czégény et al, 2016 ; Köhler et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%